MOTIVATIONAL COMPONENTS OF ADULT LEARNING WITHIN THE INFORMAL EDUCATIONAL SETTINGS - Gehtmane-Hofmane, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This study investigated the motivational components of adult learning within informal educational settings using Constructivist grounded theory methodology. The research question - what are the motivational components of adult informal learning viewed in the Equine Assisted Learning practice framework as a learning space, where primarily learning takes place. Three dominant motivational components of adult learning were identified from the study and offered for discussion. Equine-Assisted Learning as an informal learning environment incorporates motivational components that appear intrinsic over extrinsic motivation, performance over achievement, and immediate satisfaction over long-term benefit. These motivational components are detailed further through three surfaced subcategories: interest-driven learning, immediate satisfaction, and desire for the challenge.